Análise do processo de “coopetição” em uma cooperativa da indústria da construção civil do Ceará - Pinheiro, Davi Teixeira (2018)
Companies are still dominated by competition, in a win-lose based strategy, i.e. one side wins and other loses; or sometimes lose-lose in which both sides loses. On the other hand, some companies choose to cooperate as a way to countermeasure competition. Meaning the collective interest overlaps the individual one. In recent years another phenomenon has been better adapted to the business scenario. This phenomenon is called "coopetition", that is, to cooperate with the competitor. "Coopetition" has emerged for more than a century, but it has become popular in the last 20 years and is still under-researched in academia and unknown to the business scenario. There are several gaps regarding the concept, context, process and application of "coopetition" in the business scenario, despite several publications in periodicals and events that deal with the subject. This work aims to analyse the process of "coopetition" in the civil construction industry in Ceará through a case study in a purchasing cooperative, through qualitative, descriptive and exploratory research, whose data collection takes place through of semi-structured interviews and documentary research. The main results show the cooperative as a result of the union of competing companies seeking to make joint purchases of inputs in better conditions than when performed alone regarding price, time and contract. This is to cooperate in the acquisition of raw material and to compete in the sale of the product. Compete with customers and cooperate in activities away from customers.